CARRY OUT THE DIAGNOSIS AND TREATMENT OF HELMINTHIASES IN CHILDREN AND ADULTS ACCORDING TO THE TEACHINGS OF IBN SINA (World Bulletin of Public Health, 2022)
Today, parasitic diseases are one of the issues raised to the public scale. These diseases are widespread among the population, especially in children, negatively affecting their severity and, in turn, lead to serious economic damage to the social sphere. Ibn Sino's doctrine does not have any adverse effects compared to modern methods of treatment on the body's therapeutic effect. It should be noted once again that such treatment is worse for children